2019
DOI: 10.1021/acs.jpca.9b08102
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Thermal Decomposition of Hexamethyldisilane by Flash Pyrolysis Vacuum Ultraviolet Photoionization Time-of-Flight Mass Spectrometry and Density Functional Theory

Abstract: Thermal decomposition of hexamethyldisilane (HMDS) was studied from room temperature to 1310 K using flash pyrolysis vacuum ultraviolet single-photon ionization time-of-flight mass spectrometry (VUV-SPI-TOFMS). Decomposition pathways of HMDS and initial reaction intermediates were also investigated using density functional theory (DFT) at the B3LYP/6-311++G­(d,p) level. Unimolecular decomposition reactions of HMDS involving Si–Si and Si–C bond cleavage, as well as decomposition producing Me4Si and :SiMe2 via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The overall energy thresholds for these two channels were determined to be 45.5 and 44.1 kcal/mol relative to 1,1,2,2-tetramethyldisilene, respectively. Me 2 SiCH 2 then undergoes a series of secondary reactions which leads to the formation of the m / z = 68 species (reaction ), as studied previously. ,,, …”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The overall energy thresholds for these two channels were determined to be 45.5 and 44.1 kcal/mol relative to 1,1,2,2-tetramethyldisilene, respectively. Me 2 SiCH 2 then undergoes a series of secondary reactions which leads to the formation of the m / z = 68 species (reaction ), as studied previously. ,,, …”
Section: Resultsmentioning
confidence: 94%
“…Some previous studies have shown that: SiCH 2 could also be produced by a methane elimination from dimethylsilylene (:SiMe 2 ) with an energy barrier of 56.6 kcal/mol. , The m / z = 40 peak did not show up until the temperature reached 1250 K, and it could correspond to SiC which was evolved from an H 2 elimination from: SiCH 2 . The sequential H 2 loss from propane ( m / z = 44) which was produced from the propane elimination of :Si­(H)Pr could also contribute to the signal from m / z = 40–44. ,, The observations of the m / z = 28 peak at 1130 K indicated the formation of Si atoms, and they could be produced from the further reaction of SiC. , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations